PERAN DIVERSITY PROJECT DALAM MEMPERSATUKAN KEBERAGAMAN INDONESIA DI ERA GLOBALISASI - Hendi Sama; Dame Afrina Sihombing; Teddy Jurnali; Putri Salsabella; Elita Elita; Nindi Suci Rahmadani; Nur Alficha; Silfia Nadilla; Febby Febby; Kezia Yohana Zai; Surya Chandra; Tuanku Stefino (National Conference for Community Service Project (NaCosPro), 2020)
In the current era of globalization, it is very rare to find people who live in harmony with the diversity that surrounds them. As we know, developments in the current era of globalization have not been spread evenly and have not been done well. There are some people who might still not be able to understand the diversity and reversal that we must unite so that Indonesia is not divided as our motto, "Unity in Diversity" which means different but still one. Therefore, we were sent to carry out community service activities with the theme of uniting Indonesia's diversity in the era of globalization. This activity is intended to unify the diversity that exists in Indonesia with top priority in the city of Batam. This activity will motivate the community or residents of the orphanage so that in the future they will have a more peaceful life in getting along with the whole community.